Descriptive analysis of longitudinal endoscopy for exercise‐induced pulmonary haemorrhage in Thoroughbred racehorses training and racing at the Hong Kong Jockey Club. (17th September 2014) - Preston, S. A.; Riggs, C. M.; Singleton, M. D.; Troedsson, M. H. T.
Summary: Reasons for performing study: Exercise‐induced pulmonary haemorrhage (EIPH) is reported as a performance limiting condition in racehorses, yet few longitudinal studies characterising EIPH have been reported. Objectives: To characterise EIPH during training and racing in the absence of prophylactic medication with furosemide among horses imported to Hong Kong during 2007–2012. Study design: Retrospective descriptive study of clinical endoscopy, EIPH status, and racing records. Methods: Thoroughbred geldings (n = 822) imported from New Zealand between 2007 and 2012 were retrospectively assigned to 4 groups: diagnosed with EIPH via endoscopy (EIPH+), graded using recognised criteria; observed with epistaxis (Epistaxis); free of EIPH on endoscopy (EIPH‐); and those in which no endoscopy was performed. Results: The majority of horses (89%) were subjected to endoscopy once or more (median 15, interquartile range 3–18). Of those undergoing endoscopy, 55% of horses were diagnosed EIPH+ which varied in severity. Few (4%) experienced epistaxis. EIPH+ was diagnosed most frequently (63%) after racing. There was no significant difference in the proportion of EIPH+ and EIPH‐ horses that raced. Racing career longevity was longest for EIPH+ horses. The number of starts in Hong Kong for EIPH+ horses was not significantly different to EIPH‐ horses.[Correction added on 9 January 2015, after first online publication: The term 'lifetime starts' has been changed to 'starts in Hong Kong' in the preceding sentence.] Days to retirement were longer for EIPH+ horses. Horses with mild EIPH+ ( grade < 3 ) were more likely to be retired for other causes whereas severe grades (≥3) were more likely to be retired for EIPH. Conclusions: Exercise‐induced pulmonary haemorrhage is common and varies in severity between individuals and between episodes in the same individual. There is no difference in racing career longevity between EIPH+ and EIPH‐ horses trained and raced without furosemide. See also correspondences by PS Morley and KW Hinchcliff ;AD Richards; andS. Preston and C. M. Riggs Abstract : See also correspondences by PS Morley and KW Hinchcliff ;AD Richards; andS. Preston and C. M. Riggs